Data protection regulation ontology for compliance - Mlacic, Vinko (My University, 2022)
The GDPR is the current data protection regulation in Europe. A significant market demand has been created ever since GDPR came into force. This is mostly due to the fact that it can go outside of European borders if the data processed belongs to European citizens. The number of companies who require some type of regulation or standard compliance is ever-increasing and the need for cyber security and privacy specialists has never been greater. Moreover, the GDPR has inspired a series of similar regulations all over the world. This further increases the market demand and makes the work of companies who work internationally more complicated and difficult to scale. The purpose of this thesis is to help consultancy companies to automate their work by using semantic structures known as ontologies. By doing this, they can increase productivity and reduce costs. Ontologies can store data and their semantics (meaning) in a machine-readable format. In this thesis, an ontology has been designed which is meant to help consultants generate checklists (or runbooks) which they are required to deliver to their clients. The ontology is designed to handle concepts such as security measures, company information, company architecture, data sensitivity, privacy mechanisms, distinction between technical and organisational measures, and even conditionality. The ontology was evaluated using a litmus test. In the context of this ontology, the litmus test was composed of a collection of competency questions. Competency questions were collected based on the use-cases of the ontology. These questions were later translated to SPARQL queries which were run against a test ontology. The ontology has successfully passed the given litmus test. Thus, it can be concluded that the implemented functionality matches the proposed design.